HAMLET-BASED NUTMEG CULTIVATION AND PRODUCTION SYSTEM IN WEST SERAM DISTRICT, MALUKU, INDONESIA - Anna Yuliana Wattimena; Marlita Herlin Makaruku; Asri Subkhan Mahulette; Martha Amba; Esther Kembauw (International Journal of Multidisciplinary Sciences and Arts, 2023)
Most of the nutmeg cultivation systems in Maluku are smallholder plantations. Agroforestry has long been developed in Maluku for generations known as dusung. Dusung can increase farmers' income continuously because the harvest is done weekly, monthly, yearly. The problems faced by farmers in Maluku regarding the productivity potential of nutmeg plants are caused by factors such as plant age, plant cultivation techniques and conventional processing. Based on these problems, a study was conducted to obtain data and information about hamlet-based nutmeg cultivation systems and productivity in Kairatu Barat District. The data and information are useful in the context of improving hamlet-based nutmeg cultivation systems in Kairatu Barat District, West Seram Regency in the future. The research uses survey methods and direct observation in the field. The selection of respondents was carried out by purposive sampling. Respondents amounted to 32 farmers. Sampling was carried out using Stratified Random Sampling, strata were determined based on the number of nutmeg plants per farmer and samples were taken randomly from each farmer. Data collected in the form of primary and secondary data. The research was carried out during the 2022 harvest season. The results of the research indicated that the cultivation system and production of nutmeg in West Kairatu District (Kamal village, Nuruwe, Lohiatala) is classified as low. Due to the number of nutmeg plants that produce began to decline. the seeds used as seeds still come from sweeping seeds. Control of Plant Destruction Organisms is carried out only when the plants start producing and fertilization is never done. Overall, the farmers in the research location cultivate hamlet-based nutmeg plants.